Morphological and Molecular Variation in the Pumpkin Toadlet, Brachycephalus ephippium (Anura: Brachycephalidae) - Clemente-Carvalho, R. B. G.; Alves, A. C. R. [UNESP]; Perez, S. I.; Haddad, Celio Fernando Baptista [UNESP]; dos Reis, S. F. (Soc Study Amphibians Reptiles, 2011)
A recent study demonstrated marked variation in cranial shape between a population of Brachycephalus ephippium from Jundiai in São Paulo state and populations from Atibaia and Sao Francisco Xavier (São Paulo) and Macae de Cima in the state of Rio de Janeiro in southeastern Brazil. This result contrasts with earlier work describing differences in cranial shape between the population from Rio de Janeiro and those from São Paulo. Here, we investigate the nature and extent of variation between populations of B. ephippium using two lines of evidence. First, we reevaluate patterns of morphological variation by incorporating semi-landmarks into the quantitative description of cranial shape and by using scanning electron microscopy (SEM) to describe qualitative skeletal features. Second, we assess molecular variation in the mitochondrial genes cytochrome b, 12S rRNA, and 16S rRNA, and the nuclear Rag-1 gene, totaling 3,697 base pairs. Geometric analyses of cranial shape and SEM images of skeletal traits show that the population from Macae de Cima and the populations from São Paulo differ markedly in morphology and diverge in the cytochrome b, 12S, and 16S rRNA genes by 9.7%, 2.8%, and 4.4%, respectively. Divergence in the nuclear gene Rag-1 is, as expected, much lower (0.6%). These results clearly demonstrate heterogeneity between populations that are all currently diagnosed as B. ephippium and point to the need for further research to ascertain the true diversity currently hidden under the name of B. ephippium.